2019
DOI: 10.1002/alr.22478
|View full text |Cite
|
Sign up to set email alerts
|

Prescription patterns and opioid usage in sinonasal surgery

Abstract: Background Excess opioid use after surgery contributes to opiate misuse and diversion. Understanding opioid prescribing and utilization patterns after sinonasal surgery is critical in designing effective practice protocols. In this study we aim to identify factors associated with variable opioid usage and further delineate optimal prescription patterns for sinonasal surgery. Methods All patients undergoing sinonasal surgery within a single health‐care system from March 2017 to August 2018 were sent electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 23 publications
3
35
0
Order By: Relevance
“…Data on opioid usage among patients undergoing ESS and septoplasty vs ESS alone are inconsistent. One study noted that ESS with septoplasty patients did not request narcotics refills at a higher rate, 2034 while another study did show that concurrent ESS and septoplasty associated with greater opioid usage 2035 . Patients undergoing concurrent ESS and septoplasty have a longer period to pain relief than those patients undergoing septoplasty alone 2036 …”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…Data on opioid usage among patients undergoing ESS and septoplasty vs ESS alone are inconsistent. One study noted that ESS with septoplasty patients did not request narcotics refills at a higher rate, 2034 while another study did show that concurrent ESS and septoplasty associated with greater opioid usage 2035 . Patients undergoing concurrent ESS and septoplasty have a longer period to pain relief than those patients undergoing septoplasty alone 2036 …”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…Educational materials alone have been proven to be effective in increasing safe opioid storage and disposal 16,17 . Better integration of educational materials during the preoperative visit and the day of surgery could help decrease intentional and unintentional opioid diversion within the community through improved disposal 18 . Ultimately, the Food and Drug Administration recommends disposing of opioids at Drug Enforcement Administration approved sites or approved community take back programs; however, if these are not available, then flushing designated opioids is advised 19 …”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a series of 364 patients, Newberry et al found that excess narcotics were prescribed 84.9% of the time. Among patients, 11.8% reported using no narcotics, 52.1% used <50%, and 36.1% used >50% of their narcotic prescription 8 . In the pursuit of finding non‐narcotic alternatives to pain control after sinonasal surgery, Kemppainen et al 9 conducted a clinical trial that concluded acetaminophen alone is a highly effective pain treatment regimen after FESS.…”
Section: Discussionmentioning
confidence: 99%